Detection of plated-out radon progenies on CR-39 detectors - Patiris, D. L.; Ioannides, K. G.; Tsabaris, C. (HNPS Advances in Nuclear Physics, 2019)
A spectrometric study of alpha particles using CR-39 solid state nuclear track detectors is described. It is based on the application of software imposed selection criteria, concerning the geometrical and optical properties of the tracks which are created by alpha particles of specific energy falling on the detector at given angles of incidence. These selection criteria are based on a preliminary study of tracks’ parameters (major and minor axes and mean value of brightness), using the TRIAC II code. Since no linear relation was found between the energy and the geometric characteristics of the tracks (major and minor axes), we resorted to the use of an additional parameter in order to classify the tracks according to the particles’ energy. Since the brightness of tracks is associated with the tracks’ depth, the mean value of brightness was chosen as the third parameter. This method could be applied as a low cost technique in studies concerning the radon’s daughters 218Po and 214Po behavior in air.